1980
DOI: 10.1002/dev.420130206
|View full text |Cite
|
Sign up to set email alerts
|

The ontogenesis of defensive reactions to shock in preweanling rats

Abstract: Behavioral observations were made on the reaction to tailshock and footshock in 5- to 20-day-old hooded rats. For detection thresholds, age differences were found for footshock but not for tailshock. During intershock intervals, more generalized activity and freezing were elicited by footshock, whereas more responding directed to the shock source was elicited by tailshock. The unconditional responding to shock indicated that the older animals had a larger behavioral repertoire of defensive reactions and respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 13 publications
3
36
0
3
Order By: Relevance
“…Falcon et al [77] found that the nadir for thermal pain thresholds in infant rats occurred at P6 and similar age-related patterns were noted in thresholds for the cutaneous withdrawal reflex [73] and foot-shock responses [122]. When rat pups of different age groups (P4, P7, P14) were tested with graded painful stimuli in our laboratory, the number of ultrasonic cries at P7 were significantly increased (ANOVA, F = 57.94, p !…”
Section: Critical Periods Of Vulnerabilitymentioning
confidence: 99%
“…Falcon et al [77] found that the nadir for thermal pain thresholds in infant rats occurred at P6 and similar age-related patterns were noted in thresholds for the cutaneous withdrawal reflex [73] and foot-shock responses [122]. When rat pups of different age groups (P4, P7, P14) were tested with graded painful stimuli in our laboratory, the number of ultrasonic cries at P7 were significantly increased (ANOVA, F = 57.94, p !…”
Section: Critical Periods Of Vulnerabilitymentioning
confidence: 99%
“…Haroutunian and Campbell (1979) demonstrated that moderately painful shock could not support aversion learning in neonatal rat pups unless it was delivered intraperitoneally, although higher shock (>1.0 mA) readily produced an odor aversion in very young pups (Kucharski and Spear 1984;Miller et al 1990a;Sullivan and Wilson 1995). While lower shock levels are painful to pups (Stehouwer and Campbell 1978;Collier and Bolles 1980;Emerich et al 1985;Sullivan et al 2000a), they paradoxically produce an odor preference in pups younger than PN10-12 (Sullivan et al 1986;Camp and Rudy 1988), apparently due to the amygdala's failure to participate during the conditioning (Sullivan et al 2000a).These data suggest that pups have access to at least two neural pathways for odor-aversion learning, although each has a different developmental time course. To test this, we made a direct neurobehavioral comparison of LiCl-induced odor aversion, 1.2-mA shock-induced odor aversion, and the 0.5-mA shock that produces a preference in young pups but an aversion in older pups.…”
mentioning
confidence: 99%
“…Before this age, odor-shock associations paradoxically induce an odor preference (Stehouwer and Campbell 1978;Haroutunian and Campbell 1979;Camp and Rudy 1988;Sullivan et al 2000) despite pups feeling pain from shock (Collier and Bolles 1980;Barr 1995;Fitzgerald 2005). The neural network sustaining this paradoxical preference involves OB and anterior piriform cortex (aPCx) whereas the amygdala does not appear to participate in the circuit (Sullivan and Wilson 1995;Roth and Sullivan 2005;Moriceau et al 2006).…”
mentioning
confidence: 99%